Spatial Thinking Process of Curved-Sided Room Building Material for Grade V Elementary School Based on Ecomathematics - Alfarisi, Ahmad Rifqi; Fiantika, Feny Rita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to explain how the spatial thinking process of V-C grade students at SDN Kalirungkut 1 Surabaya. This study used Qualitative Approach with explorative descriptive approach. Based on the findings of this study, it states that the spatial thinking proficiency of learning in the topic of curved-sided spaces related to mathematical economics is satisfactory. The observation results show that teachers and students have achieved the predetermined indicators. This was also evident from the written test results of 26 students of class V-C where 13 students were in the high category who were able to exceed the achievement standard. Teacher and student interviews have been in accordance with teacher and student observations, as well as written tests. It can be concluded that the use of ecomathematics teaching materials in learning curved-sided space building material is a useful innovation for SDN Kalirungkut 1 Surabaya.